Thermo-oxidative behaviour of epoxidised natural rubber - Ivan G; Giurginca Maria; Jipa S; Setnescu R; Setnescu Tanta; Tavaru Erika (Journal of Natural Rubber Research, 1993)
Epoxidised natural rubber (ENR) was specially formulated for improving NR basic properties, namely its resistance to fuels and oils, gas permeability and compatibility with polar elastomers, NR with various degrees of epoxidation was submitted to accelerated ageing tests; its behaviour was observed by means of IR spectroscopy and oxyluminiscence, and its processing characteristics were evaluated in a Brabender Plastograph. The influence of the degree of epoxidation on the thermo-oxidation behaviour was investigated.
Keywords: Epoxidised natural rubber